2023
DOI: 10.3390/toxins15060383
|View full text |Cite
|
Sign up to set email alerts
|

Enniatin B1: Emerging Mycotoxin and Emerging Issues

Abstract: Although over the last 10 years several studies have focused on the emerging mycotoxins known as enniatins (ENNs), there is still a lack of knowledge regarding their toxicological effects and the development of a correct risk assessment. This is especially true for enniatin B1 (ENN B1), considered the younger sister of the widely studied enniatin B (ENN B). ENN B1 has been found in several food commodities and, as with other mycotoxins, presents antibacterial and antifungal properties. On the other hand, ENN B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As the potential immunotoxicity is a significant concern for several chemicals prioritized in PARC Work Package 5, including BPA, its analogs ( Kodila, Franko, and Sollner Dolenc, 2023 ) and certain mycotoxins ( Schmutz, Cenk, and Marko, 2019 ; Kraft, Buchenauer, and Polte, 2021 ; De Felice, Spicer, and Caloni, 2023 ), these substances will be used in addressing data gaps and advancing the development of NAMs for immunotoxicity. Additionally, PFASs serve as model chemicals for several groups in PARC, given their ability to target the immune system ( Holst et al, 2021 ; Ehrlich et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the potential immunotoxicity is a significant concern for several chemicals prioritized in PARC Work Package 5, including BPA, its analogs ( Kodila, Franko, and Sollner Dolenc, 2023 ) and certain mycotoxins ( Schmutz, Cenk, and Marko, 2019 ; Kraft, Buchenauer, and Polte, 2021 ; De Felice, Spicer, and Caloni, 2023 ), these substances will be used in addressing data gaps and advancing the development of NAMs for immunotoxicity. Additionally, PFASs serve as model chemicals for several groups in PARC, given their ability to target the immune system ( Holst et al, 2021 ; Ehrlich et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen 27 found that knockdown of the leukocidin homologous gene FOXB _16250 in Fusarium spinosum Fo5176 resulted in a reduction in the pathogenicity of the Fo5176 mutant, as well as a delay in the onset of disease when the mutant was inoculated into Columbia-type Arabidopsis thaliana wild-type plants, suggesting that leukocidin synthesis genes inhibit Fusarium spinosum pathogenicity. Enniatin is a hexapeptide fungal toxin that is present in the mycelium that can have a strong toxic effect on the cellular tissues of plants [ 28 ]. The ESYN1 gene is an important regulator of the biosynthesis of enniatin.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that ZEA poses a significant threat to the health of livestock and poultry, with strong reproductive toxicity [ 1 ] and immunotoxicity. ZEA induces excessive ROS generation in organisms [ 2 , 3 ] and can trigger severe oxidative damage in intestinal epithelial cells [ 4 ]. Cellular oxidative stress is one of the fundamental causes of damage to biomolecules such as DNA, proteins, and lipids [ 5 ].…”
Section: Introductionmentioning
confidence: 99%